1984
DOI: 10.1007/bf00291561
|View full text |Cite
|
Sign up to set email alerts
|

Human C4 polymorphism: Pedigree analysis of qualitative, quantiative, and functional parameters as a basis for phenotype interpretations

Abstract: Ten families with 82 members were investigated for C4A- and B polymorphism in a blind trial. Phenotyping was done on neuraminidase treated sera by immunofixation and simultaneously by hemolytic overlay electrophoresis. In addition Rg, Ch, BF, C2, HLA-A, B, C, DR, and GLO were determined. After decoding the samples the reliability of blind typing was found to be 84.4% according to segregation patterns. Inconsistencies occurred mostly when A4, A2, or A92 were present. The detection of silent A*Q0 and B*Q0 allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…From RM measurements the alleles were diagnosed as C4A '92', C4A 12 and the common C4A 3. A '92' was distinct in RM values from A 91 and therefore tentatively introduced pending future side-by-side comparison with a C4A 92 variant described earlier [36] but never defined in a reference exercise. A 4th band migrating in the position of C4A 2 was considered to be the minor band of A '92' since only 3 alleles appear to be expressed from C4·-chains and TaqI RFLP.…”
Section: Resultsmentioning
confidence: 99%
“…From RM measurements the alleles were diagnosed as C4A '92', C4A 12 and the common C4A 3. A '92' was distinct in RM values from A 91 and therefore tentatively introduced pending future side-by-side comparison with a C4A 92 variant described earlier [36] but never defined in a reference exercise. A 4th band migrating in the position of C4A 2 was considered to be the minor band of A '92' since only 3 alleles appear to be expressed from C4·-chains and TaqI RFLP.…”
Section: Resultsmentioning
confidence: 99%
“…crossed immunoelectrophoresis gels [13]. While scanning densitometry is more precise than visual interpretation, it has not substan tially improved the detection of C4 null al leles [23]. It may be difficult to determine heterozygous C4 nulls in samples exhibiting overlapping electrophoretic bands.…”
Section: Discussionmentioning
confidence: 99%
“…The rare exception would be the C4A1 allotpye which is Rgl negative and Chi positive and some C4B5 allotypes that are Chi negative. The frequencies of C4A1 and C4B5 are each less than 1 % and thus this should not pose a significant problem for quantitation in a Cau casian population [22], Traditional methods for the detection of relative amounts of C4A and C4B proteins have been visual inspection or densitométrie scanning of C4-allotyping gels [8][9][10][11]23] or…”
Section: Monoclonalsmentioning
confidence: 99%
“…C4A and C4B can be distinguished by specific antisera, anti-Rogers and anti-Chido respectively, and reversed correlation have been found infrequently (Giles, 1990). Mauff et al (1984) showed that the C4B protein has a higher hemolytic activity than C4A. These functional and structural differences have been determined by a sequence of four amino acids in the C4d region (Yu et al, 1988).…”
Section: Introductionmentioning
confidence: 99%